ANALISIS KINERJA KEMITRAAN INTI PLASMA PERKEBUNAN KELAPA SAWIT DI DESA JATIWARINGIN KABUPATEN KOTAWARINGIN TIMUR PROVINSI KALIMANTAN TENGAH (Performance Analysis Of The Core Plasma Partnership Of Palm Palm Plantations In Jatiwaringin Village, East Kotawaringin District, Central Kalimantan Province) - BERE, NOPRIANO; PUDJIASTUTI, AGNES QUARTINA; SETIAJI, JATMIKO (Universitas Mulawarman (University of Mulawarman), 2024)
The partnership pattern is the umbrella for all plantation business collaboration between core and plasma companies. The plasma core business partnership system for oil palm farmers is an effort to improve the welfare of farmers. The aim of the research is to determine partnership patterns, the influence of stakeholder roles, stakeholder characters, and partnership models on KUD performance and farmer welfare. The sample in the research was 81 oil palm farmers with data analysis using SEM (Structural Equation Modeling) analysis techniques. Research results Partnership patterns used by PT. Makin Group with Jatiwaringin oil palm farmers provides welfare and benefits for both parties, with a direct influence on the character of stakeholders and the role of stakeholders with p-value ≤ sig 0.05 directly influencing KUD performance. KUD performance and the role of stakeholders p-value ≤ sig 0.05 have a direct influence on farmer welfare. The indirect influence of stakeholder character, stakeholder role, and KUD performance has a p-value smaller than the sig level of 0.05 which has an indirect effect on farmer welfare. The plasma core partnership model in Jatiwaringin Village applies a partnership model managed by the Village Unit Cooperative (KUD).